The Influence of Competence, Job Satisfaction and Work-Life Balance on Employee Productivity in Companies in Bekasi - Tubagus Hedi Saepudin (Siber Nusantara of Economic and Finance Review, 2026)
This study aims to analyze the influence of competence, job satisfaction, and work-life balance on employee productivity in companies in Bekasi. The method used is a Systematic Literature Review (SLR) by integrating findings from 30 reputable scientific articles sourced from international journals indexed by Scopus, Web of Science, Elsevier, Sage, Emerald, and national journals indexed by SINTA. Literature selection was carried out using strict inclusion and exclusion criteria, with data analysis through the stages of data reduction, data presentation, and drawing conclusions strengthened by source triangulation. The results of the study indicate that: 1) Competence influences employee productivity in companies in Bekasi; 2) Job satisfaction influences employee productivity in companies in Bekasi; 3) Work-life balance influences employee productivity in companies in Bekasi.